A porous medium model for simulating conjugate heat transfer between wire-wrapped fuel bundles under forced and mixed convection. (February 2021) - Chen, Yutong; Liang, Yu; Zhang, Dalin; Wang, Shibao; Wang, Chenglong; Deng, Jian; Tian, Wenxi; Qiu, S.Z.; Su, G.H.
Highlights: A 3-D detailed porous medium model for wire wrapped fuel bundles has been proposed. The prediction results of the model proposed agree well with experimental results. The model has been validated under various conditions. The model could simulate wire-wrapped fuel bundles with low computing cost. Abstract: Wire-wrapped fuel bundles have been widely used in SFRs, and the conjugate heat transfer between wire-wrapped fuel bundles plays a key role in safety characteristics of SFRs. However, due to the existence of helical wire spacers, the geometry of fuel bundle becomes quite complicated, bringing challenges to realistic CFD modeling. A porous medium model for simulating conjugate heat transfer between fuel bundles have been proposed in this study. The geometries of fuel rods and wrapper tubes are preserved and helical wire spacers are treated as solid body of porous medium in this model. The flow resistance induced by helical wire spacers is considered by adding additional flow resistance source terms to momentum equation and the transverse mixing effects caused by wire spacers and thermal plumes are accounted by modifying diffusion terms in energy equation of porous medium model. The sodium experiment of 19-pin wire-wrapped fuel bundle under forced convection performed by ORNL and sodium experiments of multi-bundle systems named CCTL-CFR and PLANDTL-DHX under mixed convection conducted by JNC were selected as benchmark. Comparison results show that under both forced and mixed convection, this model could attain considerable accuracy in the prediction of conjugate heat transfer between fuel bundles with relatively low computational cost and have the potential to simulate core-wide temperature distribution of SFR.